1990
DOI: 10.21273/jashs.115.4.605
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Translocation, and Metabolism of Sethoxydim in Centipedegrass and Goosegrass

Abstract: Absorption, translocation, and metabolism of foliar-applied 14C-labeled sethoxydim (14C-sethoxydim) in sethoxydim-tolerant centipedegrass [Eremochloa ophiuroides (Munro) Hack.] and sethoxydim-sensitive goosegrass [Eleusine indica (L.) Gaertn.] were determined. The distribution of 14C in treated leaves indicated that similar amounts (≈ 3%) were found in the epicuticular wax fraction (chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Previous studies have reported , 2% translocation of sethoxydim from treated leaves to roots of bermudagrass, goosegrass [Eleusine indica (L.) Gaertn. ], and centipedegrass [Eremochloa ophiuroides (Munro) Hack] (McCarty et al 1990;Wills 1984), probably explaining our observed results. Elephantgrass survival decreased as the sethoxydim rate increased (Figure 3c).…”
Section: Herbicide Responsesupporting
confidence: 63%
“…Previous studies have reported , 2% translocation of sethoxydim from treated leaves to roots of bermudagrass, goosegrass [Eleusine indica (L.) Gaertn. ], and centipedegrass [Eremochloa ophiuroides (Munro) Hack] (McCarty et al 1990;Wills 1984), probably explaining our observed results. Elephantgrass survival decreased as the sethoxydim rate increased (Figure 3c).…”
Section: Herbicide Responsesupporting
confidence: 63%
“…Many herbicides need to be absorbed and translocated to active sites. Approximately 16 and 2% of sethoxydim were absorbed by leaves of centipedegrass and goosegrass, respectively, 2 h after application (McCarty et al 1990). When coapplying biocontrol agents with the herbicide in a tank mix, herbicide effects likely are less contributory in early infection stages when plant resistant responses are being mobilized.…”
Section: Effect Of Herbicide Pretreatmentmentioning
confidence: 99%
“…Both sethoxydim and clethodim have been widely used in a number of broadleaf crops for selective control of annual and perennial grasses (Derr 1987;Grichar 1991;Johnson and Frans 1991). The mechanism of selectivity of centipedegrass to sethoxydim was shown to be differential metabolism (McCarty et al 1990).…”
Section: Introductionmentioning
confidence: 99%